Infantile psoriasis treated successfully with topical calcipotriene - Neerja Puri (Our Dermatology Online, 2013)
Infantile psoriasis is a benign disease. Systemic features are rare and spontaneous remission occurs. There is a hazard of viral infection particularly in steroid treated children. Psoriasis in infancy is often more therapeutically challenging than atopic and seborrheic dermatitis. We report a case of nine month old infant treated with topical calcipotriene for infantile psoriasis who experienced greater benefit than he had with standard corticosteroid medications.